Can social comparison motivate satisficers? The role of input versus output in upward social comparison - Chan, Elaine (2022)
Companies often encourage consumers to compare their performance with others hoping that a comparison with a superior other will motivate consumers in their goal pursuit. However, upward social comparison is often more motivating for maximizers than satisficers. In this research, we take a closer look at the often understudied satisficers and show what types of social comparisons motivate them. Based on the accuracy–effort trade-off, we propose that satisficers care less about achieving more and focus more on the other side of the trade-off—exerting less effort. As a result, a comparison with a superior other who uses less input (vs. achieves more output) is more motivating for satisficers. Three studies support our prediction. Whereas maximizers are motivated by comparing themselves with others who achieve more, satisficers are motivated more by superior others who use less input. Collectively, these findings suggest a more nuanced perspective on satisficers and have implications for both maximizing and social comparison literature.